"Fossa navicularis" and "septum glandis": A "flow-control chamber" for the male urethra?. (July 2020) - Özbey, Hüseyin; Arlı, Osman Tayyar
Abstract: A clear understanding of the normal anatomy of the glanular urethra is essential for anatomical reconstruction of the male urethra. In hypospadias surgery, tubularization of the neourethra over a catheter or stent has been the standard method for decades. However, the male urethra is not a tubular structure with uniform configuration and diameter by forming a fossa (navicularis) in the glans penis. We recently investigated the structural anatomy of the glanular urethra using magnetic resonance imaging (MRI). We have shown that the male urethra does not have a uniform tubular structure and not covered by the corpus spongiosum to the end. The glanular urethra that forms the "fossa navicularis" has a wider caliber than the proximal urethra. Its vertical elliptical shape resembles a laterally compressed slit-like passage. The fossa navicularis is covered by a thin layer of fibrous tissue ("septum glandis") which is an extension of tunica albuginea of the corpus cavernosum and the corpus spongiosum. Our hypothesis is based on the results of MRI of the glanular urethra and the basic principles of fluid dynamics. We analyzed the flow dynamics of urine on this particular component of the urethra in terms of shape and structural properties. Because of its wider caliber than the proximal urethra, the glanular urethra (fossa navicularis) should cause an increase in pressure and a decrease in velocity of the urine flow. The navicular shape of the fossa and its elliptical external opening (the meatus) should allow urine to be expelled at higher flow rates and at opposite angles at the upper and lower corners which make the wave-like shape of the urine. It can be said that the changes in the volumetric form, pressure and velocity, as well as the wave-like shape of the urine flow are caused by the "fossa navicularis" covered by the "septum glandis". We propose that the "fossa navicularis" and "septum glandis" play a role as 'flow control chamber" in controlling the flow of the urine exiting the urethra, which must be taken into account for successful functional reconstruction of hypospadias.